Matter of Taste: A Sociological Analysis of the Archetypology of Food - Savona, Elena (Italian Sociological Review, 2026)
The aim of this proposal is to investigate the social relationship with food (now more complex and ambivalent than ever) as a “total social fact” (Mauss, 2016) through the theoretical perspective of the sociology of the imaginary developed by Gilbert Durand. Starting with a brief introduction defining the archetypal structure of the imaginary and its dynamic components (symbols, myths and rituals) understood as “variations” and cultural expressions of the archetype (Durand, 2013, p. 41). This paper explores the meanings attributed to food during festive practices and celebrations in which the food-sacred relationship seems to express powerful symbolic connections. It is possible to hypothesize that at the root of the current success of these peculiar moments of festive gathering and “collective effervescence” (Durkheim, 2013) lies a renewed need to regain access to a “sacred time” (Eliade, 1973, pp. 48, 49). The “nocturnal” experience of sagra offers the postmodern subject the opportunity to gratify the “perpetual and inexhaustible desire to return to the place of birth”, to its foods and related eating practices, “appeasing” the “nostalgia” that, otherwise, a departure from it can produce (Teti, 1999, p. 90). For these reasons, food festival represents the possibility of an “eternal return” (Eliade, 1959) to the place and time of one’s origins, a sensual “cult” capable of satisfying the visceral need for “sense of home” (Niola, 2022; Berzano, 2023), which makes this type of festive celebration a “re-enchanted” expression (Maffesoli, 2021a) of the archetype of the Great Mother.